INTERVENSI KEMANUSIAAN DALAM PERSPEKTIF PEMIKIRAN KOSMOPOLIT - Joko Priyono (Faculty of Law, Universitas Diponegoro, 2011)
The end of the cold war has open the opportunities to some liberal states to encourage their hegemony by strengthen of human rights principles, democracy and environment. Humanitarian intervention has obtained the legitimacy on the global level and be strengthened by the cosmopolit thinking of scholars such as Immanuel Kant, Emmanuel Levinas and Jacques Derrida. Cosmopolit approach has spawned a new principle called Responsibily to Protect (R2P). Its approach permit and legitimate states in humanitarian intervention both collectively and by Securffy Council mechanism or by another mechanism in international organization such as NATO. In order to reduce that excessive hegemony, empowering civil society has to be strengthened.